SYPL1 Inhibits Apoptosis in Pancreatic Ductal Adenocarcinoma via Suppression of ROS-Induced ERK Activation - Song, Yunda; Sun, Xuesong; Duan, Fangting; He, Chaobin; Wu, Jiali; Huang, Xin; Xing, Kaili; Sun, Shuxin; Wang, Ruiqi; Xie, Fengxiao; Mao, Yize; Wang, Jun; et al. (Frontiers in Oncology, 2020)
Synaptophysin-like 1 (SYPL1) is a neuroendocrine-related protein. The role of SYPL1 in pancreatic ductal adenocarcinoma (PDAC) and the underlying molecular mechanism remain unclarified. Here, after analyzing five datasets (GSE15471, GSE16515, GSE28735, TCGA and PACA-AU) and 78 PDAC patients from Sun Yat-sen University Cancer Center, we demonstrated that SYPL1 was upregulated in PDAC and that a high level of SYPL1 indicated poor prognosis. Bioinformatics analysis implied that SYPL1 was related to cell proliferation and cell death. To validate these findings, gain-of-function and loss-of-function experiments were carried out, and we found that SYPL1 promoted cell proliferation in vitro and in vivo and that it protected cells from apoptosis. Mechanistic studies revealed that sustained extracellular-regulated protein kinase (ERK) activation was responsible for the cell death resulting from knockdown of SYPL1. In addition, bioinformatics analysis showed that the expression of SYPL1 positively correlated with antioxidant activity. Reactive oxygen species (ROS) were upregulated in cells with SYPL1 knockdown and vice versa. Upregulated ROS led to ERK activation and cell death. These results suggest that SYPL1 plays a vital role in PDAC and promotes cancer cell survival by suppressing ROS-induced ERK activation.